Competing Uses and Access to Hydrological Resources in upstream Peasant Communities of the Canete River Watershed, Peru - Tristán Febres, María Claudia; Blundo Canto, Genowefa M.; Cruz García, Gisella S.; Quintero, Marcela; Pareja Cabrejos, Piedad (2018)
Introduction Globally, the pressure on natural resources is increasing, particularly on water. The United Nations’ Sustainable Development Goal 6 focuses on ensuring access to water and sanitation for all. Although water is vital for the survival of all living beings, the control and management of water resources entails power relations, conflicts and negotiations between stakeholders